Key performance indicators of marketing mix effectiveness in the pharmaceutical business - N. A. Lagoda (Путеводитель предпринимателя)
The article is devoted to the study of determining key performance indicators of the marketing mix effectiveness in the pharmaceutical business. The problems and contradictions in ensuring the effectiveness of marketing in pharmaceutical companies are emphasized. Theoretical and applied foundations for implementing the marketing mix in the pharmaceutical business are highlighted. The expediency of following the «5Ps» and «6Ps» marketing mix is justified due to their correspondence to the specific features of marketing in the pharmaceutical business. Based on the research, a system of key performance indicators of the marketing mix effectiveness in the pharmaceutical business is identified.